Exploring the Victimization of British Veterans: Comparing British Beliefs About Veterans With Beliefs About Soldiers. Issue 2 (April 2022) - Phillips, Rita Helena; Connelly, Vincent; Burgess, Mark
Evidence suggests that most of the UK public appreciate currently serving UK Armed Forces personnel but are less positive in their beliefs about veterans. This research examined the social representations held by civilian participants of UK veterans and serving soldiers to understand why veterans may be seen more negatively. An open-ended word association task was completed by 234 UK participants where they were asked to provide three initial responses to the words "veteran" and "soldier" and to evaluate their responses in accordance to prototypicality. The 1, 404 resultant associations were grouped into 14 thematic clusters. Using the hierarchical evocation method, the results suggest "heroizing associations" to be a defining core element for "soldier" and "veteran" but "victimizing associations" to be an element only for "veteran." Principal component analyses suggest victimizing associations are related to war and deindividuated associations; "heroizing associations" are related to characterizations of the veteran's personality. Implications and future directions are discussed.